Human Rights as a New Standard of Civilization in Weapons Control?. (November 2017) - Mathur, Ritu
This article is an attempt to explore the intersecting dynamic of human rights and weapons control from a postcolonial perspective. It seeks to bring to the fore the contested terrain of human rights discourses within which grand proclamations of "Human Rights" as a "new standard of civilization" are being championed. At the same time in the field of security studies, an effort to rejuvenate "disarmament as humanitarian action" is mobilizing scholars and activists. It is in this context that this article seeks to problematize deployment of specifically human rights–based discourses to address the problem of weapons. In this effort, it encourages scholars and activists to take note of the imperial legacy of human rights–based and civilization-based discourses. It then expresses concern with how these civilizational discourses of differences between the West and the Rest are exploited to encourage a licentious use of human rights language to acquire and maintain weapons by state and nonstate actors. This article then proceeds to express concern with a shift from anthropocentric to anthropomorphic discourses on weapons that threatens to constitute and reinforce a stratified human civilization. These reflections are undertaken to encourage scholars to think more deeply about the pernicious nature of a human rights–based discourse in the context of weapons control. It is an invitation for postcolonial scholarship to think more deeply about the intersecting discourses of human rights and weapons control and its implications for the Global South.